Common fixed point of multifunctions theorems in Cone metric spaces - Dubey, Anil Kumar; Narayan, Ashutosh; Dubey, Ravi Prakash (International Journal of Applied Mathematical Research, 2013)
In this paper, we generalize and obtain common fixed point of multifunctions in cone metric spaces. Our theorems improve and generalize of the results ([3],[9] and [10]).